2012
DOI: 10.1111/j.1753-4887.2011.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of milk-derived bioactive peptides in the treatment and prevention of metabolic syndrome

Abstract: The growing prevalence of metabolic syndrome as well as its impact on public health has garnered increased attention in recent years. As a result, metabolic syndrome is now considered one of the world's leading public health problems. Bioactive peptides deriving from milk proteins may play an important role in the prevention and treatment of metabolic syndrome and its complications via several mechanisms, such as the satiety response, the regulation of insulinemia levels and blood pressure, the uptake of free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(79 citation statements)
references
References 146 publications
(283 reference statements)
0
74
0
5
Order By: Relevance
“…Furthermore, the lack of association observed between CMRS and cheese may be, in part, explained by the higher fat, sodium, and lower potassium held by cheese compared with milk and other fluid dairy food [38]. On the other hand, the preponderance of evidence, mostly in adults, indicates that milk intake is more likely to be associated with beneficial cardiometabolic outcomes [13], [39], [40] and [41]. Few studies have shown the beneficial effects of other dairy products [10], [36] and [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the lack of association observed between CMRS and cheese may be, in part, explained by the higher fat, sodium, and lower potassium held by cheese compared with milk and other fluid dairy food [38]. On the other hand, the preponderance of evidence, mostly in adults, indicates that milk intake is more likely to be associated with beneficial cardiometabolic outcomes [13], [39], [40] and [41]. Few studies have shown the beneficial effects of other dairy products [10], [36] and [42].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging scientific findings also indicate that such milk fat components as butyric acid may favor fat oxidation and decrease glycogen use [50]. Moreover, it seems that bioactive peptides derived from milk proteins may act independently of calcium to prevent the development of cardiometabolic risk factors and its components via a wide range of mechanisms that include the satiety response, the regulation of insulinemia levels and BP, the uptake of free radicals, and the alteration of lipid profiles [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein content in yogurts made from cow’s and ewe’s milk is also different, as it is related to whey proteins and to the profile of bioactive peptides with the beneficial effects of these products [72,73]. The hypocholesterolaemic effect of whey proteins has been observed in connection with casein in an intervention study [74].…”
Section: Discussionmentioning
confidence: 99%
“…Durante los últimos años, los péptidos que forman parte del yogur han sido de gran interés a nivel científico por sus propiedades antihipertensivas, antimicrobianas, inmunomoduladoras, hipolipemiantes y una importante relación sobre la prevención de acumulación de grasa a nivel central (11).…”
Section: Proteínasunclassified